2007
DOI: 10.1097/01.pcc.0000282174.37595.4c
|View full text |Cite
|
Sign up to set email alerts
|

Extubation after cardiothoracic surgery in neonates, children, and young adults: One year of institutional experience

Abstract: OBJECTIVE:: Describe risk factors associated with successful and early extubation in the pediatric cardiac intensive care unit. DESIGN:: Retrospective chart review. SETTING:: University hospital, cardiac intensive care unit. MEASUREMENTS AND MAIN RESULTS:: Review of 212 consecutive surgical admissions from January 2003 to January 2004, excluding deaths. Preoperative, intraoperative, and postoperative variables were studied. Successful extubation was defined as no reintubation at any time during the cardiac int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
42
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 8 publications
8
42
1
1
Order By: Relevance
“…For example, upper airway obstruction leading to extubation failure has been implicated in 2-4% of patients in studies focused on children recovering from cardiac surgery. [6][7][8] Interestingly, one of these studies, 4 of 7 patients who failed extubation did so in the operating room secondary to extrathoracic upper airway obstruction, 8 indicating, as also demonstrated in our report, that patients need not be endotracheally intubated for prolonged periods of time to experience post-extubation stridor. In two studies of patients requiring tracheostomy following cardiac surgery, extrathoracic upper airway obstruction followed by tracheostomy placement occurred in 0.2% and 0.5% of patients.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…For example, upper airway obstruction leading to extubation failure has been implicated in 2-4% of patients in studies focused on children recovering from cardiac surgery. [6][7][8] Interestingly, one of these studies, 4 of 7 patients who failed extubation did so in the operating room secondary to extrathoracic upper airway obstruction, 8 indicating, as also demonstrated in our report, that patients need not be endotracheally intubated for prolonged periods of time to experience post-extubation stridor. In two studies of patients requiring tracheostomy following cardiac surgery, extrathoracic upper airway obstruction followed by tracheostomy placement occurred in 0.2% and 0.5% of patients.…”
Section: Discussionsupporting
confidence: 77%
“…Upper airway obstruction has also been implicated as important contributor to extubation failure, which has been associated with increased morbidity and mortality in this patient population. [6][7][8] In the most severe cases, tracheostomy is required to facilitate long-term recovery. [9][10][11] Current literature cites wide-ranging incidences of upper airway obstruction in the non-cardiac pediatric ICU population from 5-40%.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of this disorder includes traditional interventions such as hyperoxic hyperventilation, induced alkalosis, and inotropic support or specific treatments like inhaled nitric oxide [21]. As a result, pediatric intensivist tends to avoid EE in this group of patients and previous studies showed that preoperative PHT generally accepted as a risk factor for prolonged MV in children undergoing cardiac surgery [7,17,18]. Thirty percent of our patients had preoperative PHT.…”
Section: Discussionmentioning
confidence: 93%
“…During these hours, PICU is covered by pediatric residents. Hence, patients who underwent more complex surgeries are sometimes kept intubated over the night of the operation and extubated Previous studies showed that younger age at the time of cardiac surgery was associated with prolonged MV [17]. Neonatal and infantile age (especially younger than 6 months old) [7,17] has been recognized as a significant predictor of prolonged MV.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation